DETERMINING THE MOST IMPORTANT PHYSICAL VARIABLES FOR VOLLEYBALL PLAYERS IN SPECIALIZED SCHOOLS (ResearchJet Journal of Analysis and Inventions, 2023)
Field of physical education and sports are the human being with all the ingredients, capabilities, capabilities and knowledge, except that scientists and specialists in the field of tests and measurement have invented many and varied tools that are in line with and commensurate with all these variables that concern the same person and this does not mean that they are They reached the ultimate accuracy, and it also does not mean that there are no mistakes, so whatever we get accurate numbers of tests and measurement, the result will differ if we use a more accurate tool and this is due to the development of devices and tools used in tests and measure Preparations and motives as well as to observation errors and experimentation based on self –evaluation, Research community represents the players of specialized schools in volleyball in Iraq for the sports season 2021/2022. The research sample was chosen in the intentional way and they are players of the specialized school in Abi Al -Khaseeb. Recommendations were:- Using the tests extracted to evaluate and select the players- Extracting standard degrees and levels of the candidate tests from the global analysis- Conducting a similar study to other samples